PENGARUH PENDIDIKAN DAN PELATIHAN SERTA MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. ASURANSI JASA INDONESIA (PERSERO) - Sohib Muhammad Muhibin; Widodo (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
This study aims to know and analyze the influence of education, training, and work motivation on employee performance at PT. Asuransi Jasa Indonesia. Population and sample in this research is all employees of PT. Asuransi Jasa Indonesia has 35 employees.. The results showed there was a significant influence between education, motivation training work on employee performance at PT. Jasa Jasa Indonesia (Persero). There is a significant effect of education on employee performance in PT. Asuransi Jasa Indonesia (Persero) partially, There is significant influence of training on employee performance in PT. Service Insurance Indonesia (Persero) partially and there is a significant effect of work motivation on employee performance in PT. Service Insurance Indonesia (Persero) partially. From these results indicate that the value of these three variables affect the achievement of employee performance in PT. Service Insurance Indonesia (Persero) is optimal.